Socio-demographic characteristics and Iodine status of the school-going children of Suryodaya Municipality, Ilam - Adhikari, Babita; Adhikari, Praja (Journal of Food Science and Technology Nepal, 2020)
Iodine deficiency disorder (IDD) is a major micronutrient deficiency problem in Nepal. This study was conducted with objective to measure the Urinary iodine excretion (UIE) and attempts were made to relate urinary iodine with salt use and other sociodemographic variables of household of primary school children of Suryodaya municipality of Ilam district of Nepal. A community based cross section study was conducted in two schools of study area selected randomly (lottery method). A total of 202 school children of 6-12 years were recruited for the study to collect urine and salt samples for urine iodine content (UIC) and salt iodine content (SIC) measurement respectively and detail information of study population was achieved from their household. UIC was measured by ammonium persulphate digestion microplate (APDM) method and SIC was estimated by rapid test kit (RTK). Data were expressed in frequency, mean±SD and median (IQR) according to the nature of data. Chi-square test, Mann-Whitney U test and Kruskal-Wallis test were used to test the significance considering p≤0.05 at 95% confidence interval. It was found that Median UIC of the study population was 152.14 µg/L. Overall; it was found that 30.7% children had urine iodine level less than the normal WHO levels. The availability of adequately iodized salt was 93.1% as measured by RTK. There was statically significant association between consumed salt iodine content and urine iodine excretion level (P < 0.05).